Nutritional Calculating Application for Diabetes Mellitus Patients Based on Body Mass Index Using Fuzzy Logic - Nurdin, Muhammad Nurdin Rosyidi; Hidayati, Nurul; Sarosa, Moechammad (Politeknik Negeri Malang, 2023)
The number of patients with type II diabetes mellitus with its complications tends to increase from year to year as a result of uncontrolled diabetes. WHO and the Indonesian Endocrinology Association (PERKENI) predict that there will be a significant increase in the number of people with diabetes in the coming years and is predicted to continue to increase. DM in Indonesia from 8.4 million in 2000 to 21.3 million in 2030. Calculation of body mass index manually can certainly cause problems such as taking so long and being less efficient. One effort to prevent this problem is by designing an application that can calculate body mass index using the system. This application was built and designed with the aim of knowing the nutritional value status of diabetes mellitus patients based on body mass index. In determining the patient's nutritional value, a method is needed, one method that can draw conclusions to calculate nutritional value status with fuzzy logic based on body mass index variables which include age, height, weight, and activity. It can be concluded that the Application for Calculating Nutritional Needs for Patients with Diabetes Mellitus can display results based on Body Mass Index, with a total sample of 7 patients with type 2 diabetes mellitus. The application has also been tested for Quality of Service with a packet loss test result of 0.14% which is included in the very good category, and the delay value of 120.005 ms according to the standard is very good.